Death after 25C-NBOMe and 25H-NBOMe consumption. (October 2017) - Morini, Luca; Bernini, Marzia; Vezzoli, Sara; Restori, Mario; Moretti, Matteo; Crenna, Stefano; Papa, Pietro; Locatelli, Carlo; Osculati, Antonio Marco Maria; Vignali, Claudia; Groppi, Angelo
Highlights: First time that detected 25H-NBOMe and 25C-NBOMe in blood and urine. We developed an LC–MS/MS method for NBOMes detection in biological fluids. An important case report on NBOMes hallucinogenic effects. A possible interaction between different drugs of abuse is evaluated. Abstract: A teenager male was found dead in a waterway after he was spotted jumping off into the water stream. The boy looked agitated and confused after a party with friends. At the gathering place, investigators seized packages of blotter papers. A complete autopsy and a histological evaluation of the main tissues were performed; although the death occurred by drowning, the prosecutor requested toxicological exams, in order to evaluate the potential role of drugs of abuse in the episode. Blood (both peripheral and central) and urine samples as well as seized blotter papers were collected and analyzed as follows. The blotter paper, analyzed through a GC–MS method, revealed the presence of 25-NBOMes. A liquid chromatography tandem mass spectrometric (LC–MS/MS) system was used to identify and quantify 5 different 25-NBOMes (namely 25B-NBOMe, 25C-NBOMe, 25D-NBOMe, 25H-NBOMe, 25I-NBOMe) in blood and urine. 25E-NBOMe was used as internal standard (IS). 1 mL of urine and 1 mL of blood (both peripheral and cardiac) were diluted in 2 mL phosphate buffer at pH 6.0, containing IS and purified on a solid phase extraction (SPE) cartridge. LOD and LOQ for the five 25-NBOMes were calculated at 0.05 and 0.1 ng/mL respectively. Linearity, accuracy, precision, ion suppression, carry over and recovery were tested and all parameters fulfilled the acceptance criteria. Blood and urine provided positive results for 25C-NBOMe and 25H-NBOMe. Eventually, the seized blotter papers were analyzed by means of LC–MS/MS and the presence of the two NBOMes was confirmed: 25C-NBOMe and 25H-NBOMe were measured at the concentration of 2.80 and 0.29 ng/mL in peripheral blood, of 1.43 and 0.13 ng/mL in central blood and of 0.94 and 0.14 ng/mL in urine, respectively. THC and THCCOOH were also detected in biological fluids, at the concentration of 15.5 and 56.0 ng/mL in peripheral blood, 9.9 and 8.5 ng/mL in central blood, respectively. NBOMes can produce severe hallucination even at very low doses, and the 25C-NBOMe levels measured in the subject's blood are considered potentially toxic.